PREGNANCY LOSS IN WOMEN WITH HIV IS NOT ASSOCIATED WITH HIV MARKERS: DATA FROM A NATIONAL STUDY IN ITALY, 2001-2018 - Marco Floridia; Giulia Masuelli; Beatrice Tassis; Enrica Tamburrini; Valeria Savasi; Matilde Sansone; Arsenio Spinillo; Giuseppina Liuzzi; Anna Degli Antoni; Serena Dalzero; Laura Franceschetti; Giuliana Simonazzi; et al. (Mediterranean Journal of Hematology and Infectious Diseases)
Background: There is limited information on pregnancy loss in women with HIV, and it is still debate whether HIV-related markers may play a role.